Sytuacja Kościoła katolickiego w Królestwie Polskim po Rewolucji 1905 r. - Jemielity, Witold (Prawo Kanoniczne, 2005)
Three periods could be observed in the Congress Kingdom of Poland considerable political freedom until November uprising, severe restrictions for the citizens after 1831, and unification with the Russian Empire after January uprising. During each of these periods the Catholic Church experienced new situation, however the second half of the century happened to be the hardest. 1905 was the turning-point in tsar’s policy in which political situation in the country had considerable contribution. The government made two important concessions: both languages Russian and Polish could be used as official ones, and, on 17/30 of April the so called tolerant ukase was issued that concerned religious matters. The Catholic Church in the Congress Kingdom of Poland gained more freedom. The Author of the following work showed this in the separate fields of work connected with ministering to a parish such as: keeping files of records, priests’ dwellings, appointing and moving priests, bishop’s inspections, church processions, parish indulgences, change of the parish boundaries, church building, retreats and Congregations of the clergy, the Pope’s jubilee, contacts with Rome, convents, Greek Catholics, wayside crosses, Russian language in church institutions, religion lessons at schools, voting to the Russian Parliament, the tsar and social matters. The Author has been dealing with the problem of Church history in the Congress Kingdom of Poland for many years. The present work summarizes the settlements the author has obtained hitherto and especially pays attention to changes that occurred after the year 1905.